Green synthesis of silver nanoparticles using aqueous extract of Acacia cyanophylla and its antibacterial activity - Joud Jalab; Wassim Abdelwahed; Adawia Kitaz; Rawaa Al-Kayali (Heliyon, 2021)
Aims: The aim of this research is to conduct green synthesis of silver nanoparticles in an eco-friendly, economical and more effective approach using Acacia cyanophylla plant extract as well as to study the effects of the preparation conditions on the size of synthesized nanoparticles and its antibacterial activity. Methodology: In this study, silver nanoparticles have been synthesized by reduction method using aqueous silver nitrate solution and aqueous extract of Acacia cyanophylla. Then, their characterization has been studied by several methods, such as visual inspection, UV–Vis spectroscopy, dynamic light scattering and scanning electron microscope. In addition, the effects of (silver nitrate: extract) ratio, type extract, temperature and reaction time have been studied on the size of prepared silver nanoparticles. Furthermore, the antibacterial effect of these nanoparticles was studied on Escherichia coli using micro-dilution method and determination the Minimum Inhibitory Concentration (MIC). Results: The results showed that the silver nanoparticles prepared using Acacia cyanophylla extract have reported visible yellowish brown color formation and the absorption peak at 460 nm indicated the biosynthesis of silver nanoparticles. Moreover, they have average diameter (88.11) nm and the polydispersity index (PdI) was suitable. The optimal conditions for synthesis silver nanoparticles were using aqueous extract in 9:1 ratio (silver nitrate: extract) at 35 °C for 48 h. These silver nanoparticles were stable in the in the fridge at 5 °C for a maximum period of 15 days. On the other hand, the antibacterial tests showed that these nanoparticles have high antibacterial activity where the MIC value ranged between (3.125–12.5) μg/ml on E. coli isolates. Conclusion: We conclude that Acacia cyanophylla extract is considered effective as a reducing agent for the preparation of stable silver nanoparticles in certain conditions and this silver nanoparticle has a high antibacterial activity.